The Strategic Management of Research and Development - Nodoushani, Omid; Nodoushani, Patricia (Journal of Comparative International Management)

(untitled) (Management Futures, 2002)
ABSTRACT Research and Development has changed forever. At one time, laboratories were filled with PhDs who were hired by corporations to develop new technology and address a very general, perceived future need. Today, all that has changed. R & D has become a strategic, competitive tool for corporations to gain market, as well as market share, through new products or innovative processes. In this paper we discuss the R&D challenges that corporations are facing for developing a competitive strategy in an age of global capitalism.